Analysis of the Influence of Customer Perceptions of the Ease-of-Use Digital Electronic Money on Intention to Use Digital Wallet Application Ovo - Sudirjo, Frans; Dharmawan, Donny; Hardayu, Audisty Prana; Nurcholifah, Ita; Kurniawan, Yohanes Jhony (Jurnal Informasi dan Teknologi, 2023)
The purpose of this study is to ascertain how students' attitudes about electronic money affect their desire to use e-wallets. This study employs a descriptive-quantitative methodology. In this study, a survey method was employed. All of the participants in this study were students. A proportionate stratified random sample strategy was employed in this study. The following methods of gathering data were employed in this study: questionnaires, interviews, and documentation. The coefficients table shows that this study used the Windows version of SPSS to calculate the regression. The analysis and debate revealed that students' attitudes toward electronic money have a big impact on whether or not they are interested in utilizing e-wallets. The results of a basic linear regression analysis test demonstrate this, indicating that H0 is rejected if sig ≤ 0.05 with a sig value of 0.001. This is also consistent with the coefficient of determination test results, which indicate that the R square value is 0.16. It may be concluded that students' opinions about electronic money and enthusiasm in utilizing e-wallets are influenced by 16%. Technological innovation, perceived benefits, and perceived convenience all have a big impact on interest in utilizing e-wallets.